Assessment, Evaluation and Monitoring of Teaching and Learning in Nigeria Primary Schools: Challenges and Implications for Teachers - Osiesi, Mensah Prince (Utamax : Journal of Ultimate Research and Trends in Education, 2023)
Teaching and learning processes in Nigeria primary schools are worth a continuous assessment, monitoring and evaluation, as it is imperative that teachers and learners be abreast of the outcomes of their teaching-learning outcomes. This paper x-rayed the imports of assessment, monitoring and evaluation of teaching and learning processes in primary schools in Nigeria; and the many challenges militating against their successful implementation at the level. The implications of these challenges especially for teachers were itemized. The paper concludes that for improved, effective, and sustainable teaching-learning interventions, regular, effective and efficient assessment, monitoring, and evaluation practices should be implemented and sustained in all primary schools; while the challenges militating against the assessment, monitoring and evaluation of teaching and learning in Nigeria primary schools be fully addressed.